QUALITY OF WORK LIFE IN BUMN (Case Study at PLN Persero Pemangkat) - Singgih Tiwut Atmojo; erik sudarso; andy rinastopo (Department of Management - Institut Shanti Bhuana, 2020)
Abstract PT PLN (Persero) Rayon Pemangkat is a state-owned company tasked with distributing electricity and providing services to the public. PLN Rayon Pemangkat, Singkawang Area, West Kalimantan Region. PLN Rayon Pemangkat has two Units namely the Tebas and Sentebang Units. The purpose of this study is to look at the effect of Quality of Work Life (QWL) on performance. The population of this research is all of the employees of PLN Pemangkat rayon, amounting to 109 people with the study sample using a census. Data analysis using SPSS V22, the results of the t test show that QWL (X) significantly affects Employee Performance (Y) with a significance level of 0,000 <0,005 or H1 accepted. Then based on the regression results it is known that the coefficient of determination (R Square) is 0.511. This means that 51.1 percent of the performance of PLN Pemangkat staff is influenced by Quality of Work Life, while the remaining 48.9 percent is influenced by other variables outside the variables in this study. The advice given is, to maintain the performance of employees to remain good, then PLN Rayon Pemangkat must continue to improve the quality of work life of their employees in order to jointly achieve company goals. Keywords : QWL, Job Performance